Radioactive wastewater treatment using a mixture of TANNIX sorbent and VARION mixed bed ion exchange resin. (21st December 2006) - Patzay, G.; Tilky, P.; Schunk, J.; Pinter, T.; Feil, F.; Hamaguchi, K.; Weiser, L.
A wastewater treatment system has been developed by using a mixture of ammonium-insoluble tannin (TANNIX, this is the trademark of an adsorbent made by Mitsubishi Nuclear Fuel Co. Ltd) and mixed (strong acid cation exchanger and strong base anion exchanger) ion exchange resin (MIX) for the selective separation of transuranium isotopes, including Pu, Am, Cm, and U, as well as fission and radioactive corrosion products from boric acid solution (pH ∼ 4.1). The equilibrium and fixed bed sorption experiments resulted in Kd values of 10 4 –10 5 ml/g, and decontamination factors of 1, 000, with a breakthrough point between 1500 BV and 5000 BV of accumulated volume.